Preharvest Treatment Using Fungicides for Control Phytophthora Fruit Rot of Durian - Sakda Bannaphoomi; Chainarong Rattanagreetakul; Vichai Korpraditskul; Somsith Chomenansilpe; Amornrut Bhandhufalck (Agriculture and Natural Resources, 1994)
The efficacy of fungicide on Phytophthora fruit rot of durian “Cv. Mon Thong” was carried out under field condition at Chanthaburi Province. Each chemical was applied only once at one month as preharvest treatment. Two experiments were carried out in May and July, 1993. After harvest, durian fruits were ripened at room temperature. Fruit rot disease was recorded at two-days interval for 5 times. The mean occurrence of the disease from two experiments revealed that all rates of RIDOMILR MZ 72 WP (metalaxyl 8% + mancozeb 64%), i.e. 144, 180 and 216 g.ai/hl, and fosetyl-Al 200 g.ai/hl gave a similar control, i.e. 20, 15, 17.5 and 22.5% infection, respectively. They were signifecantly superior to the nontreated (37.5% infection) control. In addition, it was also observed that the amount of rainfall and the distribution of raining days influenced the efficacy of the fungicides tested.